Application of Mountain Tread Traditional Game and Fibonacci Concept in Developing Creative Thinking in Geometry Learning in Elementary School - Marcella Wijayanti Windyatmoko; Tri Isti Hartini (Lembaran Ilmu Kependidikan, 2025)
Geometry learning at the elementary school level is often considered boring and uninteresting, due to monotonous teaching methods and lack of linking the material to everyday life. To increase students' interest, creativity and understanding, this research integrates the modified traditional  Mountain Tread games with the concept of Fibonacci. This approach uses qualitative research methods with data collection through observation, interviews, and documentation during the learning process. The results show that this strategy is able to improve students' understanding of geometric shapes and patterns, as well as stimulate creativity in making patterns and exploring geometric shapes. In addition to providing a fun learning experience and increasing self-confidence, this approach also enriches the development of innovative learning methods based on local culture and modern mathematical concepts. Thus, this study shows that the integration of traditional games and Fibonacci concepts is effective in improving creativity and understanding of geometry at the elementary school level.